Understanding the Factors Influencing Chitosan-Based Nanoparticles-Protein Corona Interaction and Drug Delivery Applications - Moraru, Cristina; Mincea, Manuela; Menghiu, Gheorghita; Ostafe, Vasile (Molecules (Basel, Switzerland), 2020)
Chitosan is a polymer that is extensively used to prepare nanoparticles (NPs) with tailored properties for applications in many fields of human activities. Among them, targeted drug delivery, especially when cancer therapy is the main interest, is a major application of chitosan-based NPs. Due to its positive charges, chitosan is used to produce the core of the NPs or to cover NPs made from other types of polymers, both strategies aiming to protect the carried drug until NPs reach the target sites and to facilitate the uptake and drug delivery into these cells. A major challenge in the design of these chitosan-based NPs is the formation of a protein corona (PC) upon contact with biological fluids. The composition of the PC can, to some extent, be modulated depending on the size, shape, electrical charge and hydrophobic/hydrophilic characteristics of the NPs. According to the composition of the biological fluids that have to be crossed during the journey of the drug-loaded NPs towards the target cells, the surface of these particles can be changed by covering their core with various types of polymers or with functionalized polymers carrying some special molecules, that will preferentially adsorb some proteins in their PC. The PC’s composition may change by continuous processes of adsorption and desorption, depending on the affinity of these proteins for the chemical structure of the surface of NPs. Beside these, in designing the targeted drug delivery NPs one can take into account their toxicity, initiation of an immune response, participation (enhancement or inhibition) in certain metabolic pathways or chemical processes like reactive oxygen species, type of endocytosis of target cells, and many others. There are cases in which these processes seem to require antagonistic properties of nanoparticles. Products that show good behavior in cell cultures may lead to poor in vivo results, when the composition of the formed PC is totally different. This paper reviews the physico-chemical properties, cellular uptake and drug delivery applications of chitosan-based nanoparticles, specifying the factors that contribute to the success of the targeted drug delivery. Furthermore, we highlight the role of the protein corona formed around the NP in its intercellular fate.